2019
DOI: 10.2147/ott.s216161
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Roles And Signaling Pathways Of Phosphatidylethanolamine-Binding Protein 4 In Tumors</p>

Abstract: Phosphatidylethanolamine-binding protein 4 (PEBP4) has been found to be highly expressed in many tumors and to be closely related to the proliferation, differentiation, and metastasis of tumors. PEBP4 has also been found to be involved in many canceractivated signaling pathways and to cause therapeutic resistance. In this study, we first reviewed the morphological structure and expression of PEBP4, then discussed the roles of PEBP4 in individualized treatment of some cancers, and finally explored the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…As multiple studies have demonstrated, dysregulation of metabolism is considered one of the hallmarks of cancer in general [ 29 ], and aberrant metabolism of different lipids classes is among the main metabolic disorders in cancer cells [ 30 ]. The importance of phospholipid in metabolic alterations within BC has been explored in a few works [ 31 , 32 , 33 , 34 ], and it seems to correlate with our findings. Phospholipids synthesis is frequently increased in BC, and it has been related to oncogenesis and tumor progression [ 31 ]; particularly, an increase in PE plays a major role in some BC tumors [ 31 , 32 ].…”
Section: Resultssupporting
confidence: 85%
“…As multiple studies have demonstrated, dysregulation of metabolism is considered one of the hallmarks of cancer in general [ 29 ], and aberrant metabolism of different lipids classes is among the main metabolic disorders in cancer cells [ 30 ]. The importance of phospholipid in metabolic alterations within BC has been explored in a few works [ 31 , 32 , 33 , 34 ], and it seems to correlate with our findings. Phospholipids synthesis is frequently increased in BC, and it has been related to oncogenesis and tumor progression [ 31 ]; particularly, an increase in PE plays a major role in some BC tumors [ 31 , 32 ].…”
Section: Resultssupporting
confidence: 85%
“…In addition, PEBP4 is reported to be involved in the activation of sonic hedgehog (SHH) pathway (Jian et al, 2019). These research indicate that PEBP4 is potentially involved in many molecular pathways to modulate tumor pathogenesis (Luo et al, 2019), but its potential role in other diseases like hepatic fibrosis has not yet been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatidylethanolamine-binding protein 4 (PEBP4) is a newly discovered secreted protein of the PEBP family, and is expressed in multiple human tissues such as the heart, lung, colon, prostate, and liver (He et al, 2016;Luo et al, 2019). Existing studies have revealed the effects of PEBP4 on multiple human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the inhibition of apoptosis induced by tumor necrosis factor-α (TNF-α) and the upregulation of hPEBP4 plays a vital role in tumor progression in various types of cancer [ 26 , 27 , 28 , 29 ]. Qiu et al investigated hPEBP4 as an independent biomarker for predicting rectal cancer response to radiotherapy treatment ( p = 0.001).…”
Section: Resultsmentioning
confidence: 99%